STUDI KARAKTERISTIK KELISTRIKAN KOMPOSIT CARBON NANOTUBE-POLYVYNILIDENE-FLOURIDE (CNT-PVDF) - Maulidanir Rohman; Agus Subagio (Youngster Physics Journal, 2013)
Development of nanomaterial technology strongly supports advancements in composite technology. Composite that use nanomaterial produce better electrical properties than common composite. Carbon nanotubes (CNT) is one of nanomaterial with high conductivity, so it’s potentially used in composite for various aplication. This research combines Carbon Nanotubes (CNT) with Polyvynilidene Flouride (PVDF) for producing CNT-PVDF composite with high conductivity. CNT-PVDF composites were fabricated by solution processing method. PVDF was dissolved into distillated aceton then CNT was dissolved in acetone and added Triton X-100 4 ml. PVDF solution and the solution of CNT were stirred for 1 hour using a magnetic stirrer, then both were mixed and stirred at temperature of 40 ° C until the acetone evaporates. Composites were molded using a hot-pressing at a pressure of 1 MPa and a temperature of 200oC for 10 minutes. CNT-PVDF composite were characterized by a conductivity test to generate conductivity values​​. The results of the analysis of the test showed that the addition of CNT conductivity on CNT-PVDF composite increased conductivity values​​. In the mass percentage of CNT 2%, 4%, 6%, and 8% conductivity increased slowly. Improved high conductivity of CNTs obtained in the mass percentage of 10%. Key word : Carbon Nanotubes, Polyvynilidene Flouride, composite, and conductivity